Towards characterizing the adaptive capacity of farmer-managed irrigat ion systems: learnings from Nepal - Thapa, Bhuwan; Scott, Christopher; Wester, Philippus; Varady, Robert (Environmental change assessments, 2016)
Small-scale irrigation systems managed by farmers are facing multiple challenges including competing water demand, climatic variability and change, and socioeconomic transformation. Though the relevant institut ions for irrigation management have developed coping and adaptation me chanisms, the intensity and frequency of the changes have weakened the ir institutional adaptive capacity. Using case examples mostly from Ne pal, this paper studies the interconnections between seven key dimensi ons of adaptive capacity: the five capitals (human, financial, natural , social, and physical), governance, and learning. Long-term adaptatio n requires harnessing the synergies and tradeoffs between generic adap tive capacity that fosters broader development goals and specific adap tive capacity that strengthens climate-risk management. Measuring and addressing the interrelations among the seven adaptive-capacity dimens ions aids in strengthening the long term sustainability of farmer-mana ged irrigation systems.